The Influence of Knowledge Management and Creativity on Employee Performance of Creative Industry in Bandar Lampung - Dias Novita Sari; Ribhan Ribhan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study investigates the impact of knowledge management and creativity on employee performance within the creative industry sector in Bandar Lampung. Employing a quantitative methodology, data were gathered through the distribution of structured questionnaires. The research sample comprised 140 employees representing various subsectors of the creative industry, including application development, architecture, interior design, visual communication design, product design, fashion, film, photography, handicrafts, culinary arts, music, publishing, advertising, performing arts, fine arts, television, and radio. To examine the relationships between the independent variables and the dependent variable, multiple linear regression analysis was utilized. The findings indicate that both knowledge management and creativity exert a positive and statistically significant effect on employee performance. This implies that enhanced knowledge management practices and elevated levels of employee creativity contribute to improved work outcomes. Consequently, organizations are encouraged to enhance their knowledge management frameworks and cultivate a creative work environment to boost employee productivity and support the achievement of organizational objectives.